PERFORMANS PRODUKSI TERNAK BABI YANG MENGKONSUMSI LIMBAH ORGANIK PASAR - Redempta Wea (Politeknik Pertanian Negeri Kupang, 2010)
The aim of this research was to evaluation growth respon, morbiditas, and the best of feed formulation which use market organic waste.The research was designed using Block (Randomly) Design with 5 treatments and 3 replications. The treatments were T0: Ration without usage of market organic waste; T1, T2, and T3, and T4: usage of 25, 50, 75, and 100% of market organic wasteÂ respectively. The result revealed that the treatments did not significantly affectÂ (P>0,05) daily gain but significantly affect (P<0,01) to dry matter intake so the mount swine morbiditas if consuming young white mustard vegetable waste 100% at treatment of T3 and of T4 and 0% at treatment of T0,T1, and T2. It can be concluded that the best feed formulation which the best of the growth, low morbiditas is T2 with using 50% market organic waste and 50% complete feed. It is suggested that usage of market organic waste in feed of pig livestock shall not exceed 50% and avoid usage of white mustard vegetable waste which still young in order not to happened diarrhoea.Keywords: Performance of production; swine; market organic waste